Higher Pathological Complete Response Rate of Less than 10 Total Axillary Lymph Nodes After Axillary Lymph Node Dissection Following Neoadjuvant Chemotherapy in Breast Cancer - Lee, Jeeyeon; Park, Nora Jee-Young; Kang, Byeongju; Jung, Jin Hyang; Kim, Wan Wook; Chae, Yee Soo; Lee, Soo Jung; Kim, Hye Jung; Park, Ji-Young; Park, Ho Yong (Frontiers in Surgery, 2022)
Background: AJCC guideline recommends the evaluation of ≥10 axillary lymph nodes (ALN) in breast cancer patients to assess N stage. However, total ALN count in ALN dissection (ALND) often decreased after neoadjuvant chemotherapy in breast cancer. The authors compared clinicopathological factors and oncological outcomes between <10 vs ≥10 ALNs after ALND following neoadjuvant chemotherapy in breast cancer. Methods: Data of 159 breast cancer patients treated with neoadjuvant chemotherapy and ALND were reviewed and the cases were classified into 2 groups (<10 vs ≥10 ALN count). Treatment response was determined based on the RECIST 1.1 criteria and histopathological regression of tumor was assessed based on the Miller-Payne grading scales. Results: Most clinical and pathological factors did not demonstrate any statistical differences between the 2 groups. However, the pathological complete response(pCR) rate in breast lesion and ALNs were higher trend in the group with less than 10 ALNs. During the 88-month follow-up period, there was no statistical difference in locoregional recurrence, distant metastasis, or overall survival. Conclusions: Although there was a limitation due to different sample size, additional axillary surgery may not be necessary even in cases with less than 10 total ALNs after ALND following neoadjuvant chemotherapy. Because the lymph nodes are more likely to have been regressed themselves due to neoadjuvant chemotherapy and the residual lymph nodes may be absent.